Dielectronic recombination data for dynamic finite-density plasmas - XIII. The magnesium isoelectronic sequence - YUMAK YAHŞİ, AYŞE; YAVUZ, İLHAN; ALTUN, ZİKRİ (EDP SCIENCES S A, 2007)
We have calculated total and partial final- state level- resolved dielectronic recombination ( DR) rate coe. cients for the ground and metastable initial levels of 21 Mg- like ions between Al+ and Xe42+. This is the final part of the assembly of a levelresolved DR database necessary for modelling dynamic finite-density plasmas within the generalized collisional-radiative framework. Calculations have been performed in both LS-and intermediate coupling, allowing for. n = 0 and. n = 1 core- excitations from ground and metastable levels. Complementary partial and total radiative recombination RR coeficients have been calculated for the same ions viz. Al+ through Zn18+, as well as Kr24+, Mo30+, and Xe42+. Fitting coeficients which describe the total RR and DR rate coeficients (separately) are also presented here. Results for a selection of ions fromthis sequence are discussed, and compared with existing theoretical and experimental results. A full set of results can be accessed from the Atomic Data and Analysis Structure (ADAS) database or from the Oak Ridge Controlled Fusion Atomic Data Center (http://www-cfadc.phy.ornl.gov/data_and_codes). The complexity of further M-shell sequences, both from the atomic and modelling perspectives, renders this juncture a natural conclusion for the assemblage of the partial database. Further M-shell work, has and will, focus more on total rate coe. cients, rather than partials, at least in the medium term.
Keywords: atomic data; atomic processes; plasmas; ELECTRON-ION RECOMBINATION; ACTIVE GALACTIC NUCLEI; OPTICALLY THIN PLASMAS; X-RAY-ABSORPTION; IONIZATION EQUILIBRIUM; RATE COEFFICIENTS; LOW-TEMPERATURES; EMISSION RATES; M-SHELL; FE-XIV